The legal status of the OECD commentaries - Douma, Sjoerd; Engelen, F. A. (Amsterdam : IBFD, 2008)
Since the mid-1980s, the legal basis of the practice of tax administrations and courts around the world to conform to the Commentaries when interpreting and applying bilateral tax treaties based on the OECD Model has been the subject of an ongoing academic debate. Recently the debate has received new impetus, and the primary focus is now on the general principles of international law. In particular, opinions differ on the question whether the Commentaries can be a source of legal obligations through the principles of acquiescence and estoppel, both of which are founded on considerations of good faith, and equity and provide specific protection of settled expectations. The reports contained in this book address two questions. The first is whether, under international law, the states parties to a tax treaty are legally bound by the OECD Commentaries when interpreting and applying the provisions of the treaty which are identical to those of the OECD Model. The second question is whether, under the contracting states' internal law, taxpayers and the tax authorities are equally bound to apply the Commentaries if and when the contracting states themselves are so bound under international law. The book brings various legal disciplines - public international law, international tax law, Community law and constitutional law - together in order to resolve the legal status of the Commentaries. Through interdisciplinary debate, the issues have been defined clearly and the exact points at which the opinions differ are identified, thereby resulting in a better understanding of the issues at hand.
Skating on thin ice? On the law of international organizations and the legal nature of the Commentaries on the OECD Model Tax Convention / Blokker, N. ; p. 13-27
Includes bibliographical references.
Keywords: Organisation for Economic Co-operation and Development; Organisation for Economic Co-operation and Development; Double taxation -- Treaties -- Interpretation and construction; Income tax -- Law and legislation -- Interpretation and construction; 2; Droit international; 2; Droit fiscal international; 2; Double imposition; Double taxation; Income tax -- Law and legislation -- Interpretation and construction; Doppelbesteuerungsabkommen; Internationales Steuerrecht; Interpretation; Internationaal belastingrecht; Modelverdragen; OESO; Kongress -- Leiden -- 2006.; Kongress; Leiden (2006)